Pengaruh Program Penanggulangan Penyakit Kronis (PROLANIS) terhadap Kadar Gula Darah Pasien Diabetes Melitus Tipe 2 - Franciscus Cahyo Kristianto; Devi Lina Sari; Aguslina Kirtishanti (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2021)
Introduction: According to the International Diabetes Federation (IDF) in 2019, it is predicted that the number of people with diabetes mellitus (DM) will increase by 51% in 2045 globally. DM leads to complications in all parts of the body and affects the quality of life. Prevention of complications has been carried out by Indonesian Health Insurance (BPJS) through the Chronic Disease Management Program (PROLANIS), with the aim that chronic disease participants can achieve optimal quality of life, one of which is marked by controlled blood sugar levels. Objective: The purpose of this study was to analyze the effect of PROLANIS on patient compliance in taking the medication and controlling the patient's blood sugar. Method: The research method used an observation design for two groups of type 2 DM patients, (1) patients who participated in the Chronic Disease Management Program and (2) patients who did not follow the Chronic Disease Management Program, to then analyze the level of adherence and blood sugar levels on day 0. and the 30th. Data analysis using Chi-square test. Results and discussion: The results of this study showed that on the 30th day, the blood sugar levels of the two groups of patients with type 2 diabetes were different (p=0.019), the risk of uncontrolled blood sugar levels in the group taking the Chronic Disease Management Program was 0.53 times lower than the group. who did not follow the program (risk ratio=0.53). Conclusion: It can be concluded that there is a relationship between patient participation in the Chronic Disease Management Program and medication adherence so that it has an impact on controlling the patient's blood sugar levels.